Art cloth : a guide to surface design for fabric - Dunnewold, Jane, 1954- (Interweave Press, 2010)
Synopsis: When Jane Dunnewold's book complex Cloth was published in 1996, it quickly became the bible of surface design for fiber artists. In the years since, the world of surface design has significantly expanded: now fiber artists, art-to-wear designers, and art quilters have a much broader range of surface design products to choose from, and there are a wealth of technique combinations that can be used to create art cloth. Art Cloth picks up where Complex Cloth left off, showing how to layer processes with the latest products to create stunning cloth for use in a variety of fiber art. Following Jane's techniques with step-by-step photography, you will learn to create art cloth using dyes, color removing agents, paints, and foils combined through processes that include silk-screen printing, stamping, stenciling, and hand painting. In addition to detailed step-by-step wet-media surface design techniques, Jane demonstrates how the use of color and design contribute to successful layering. She guides and inspires artists to take their art cloth to the next level through sidebars with design tips and exercises that support the technical information. Finally, each technique chapter concludes with project ideas for the skills learned, so anyone working through the book can literally build layers on cloth as each chapter is completed.